Elimination of harmonics in a five-level diode-clamped multilevel inverter using fundamental modulation - Ozdemir, Sule; Ozdemir, Engin; Tolbert, Leon M.; Khomfoi, Surin (My University, 2007)
In this study, elimination of harmonics in a fivelevel diode-clamped multilevel inverter (DCMLI) has been implemented by using fundamental modulation switching. The proposed method eliminates harmonics by generating negative harmonics with switching angles calculated for selective harmonic elimination method. In order to confirm the proposed method, first Matlab/Simulink and FSIM simulation results are given. Then the proposed method is also validated by experiments with Opal-RT controller and a 10 kW threephase, five-level DCMLI prototype. © 2007 IEEE.
Keywords: And multilevel inverter; Fundamental switching; Harmonic elimination